Repression among foreign workers in Malaysia / Syarmin Nor Era Omar, Rozalli Hashim and Zaliha Hj Hussin - Omar, Syarmin Nor Era; Hashim, Rozalli; Hj Hussin, Zaliha (Universiti Teknologi MARA, Shah Alam, 2017)
Hazardous, dirty and dangerous workplace; wage and safety violations; employer threats; and violating rights are among the repression condition that faced by the foreign workers in Malaysia. Similar trends can be observed in other countries as well. This paper focuses on the repression faced by foreign workers in Malaysia and suggesting that foreign workers who undergo legalization process can reduce their repression significantly. Since they can enjoy rights as a legal worker, the employer would not treat them abusively. In mid 1980s, the Malaysian government formulated policies to deal with large number of foreign workers including illegal immigrants. Among the policies are levy payment, work permit, minimum wage, i-card, legalization and amnesty. One of the most popular policies is legalization. Many developed countries such as United States, European Union and United Kingdom had implemented legalization of illegal immigrants for mostly, economic benefits. In Malaysia, there are series of legalization efforts for illegal immigrants. Legalization can be used as a tool to change the status from illegal to legal worker in Malaysia. Repression and repression related deprivations can be reduced significantly and a conducive climate of life and work is achievable.